2014
DOI: 10.1021/jo501924u
|View full text |Cite
|
Sign up to set email alerts
|

The Total Syntheses of Basiliolide C, epi-Basiliolide C, and Protecting-Group-Free Total Syntheses of Transtaganolides C and D

Abstract: The total syntheses of basiliolide C and previously unreported epi-basiliolide C are achieved by an Ireland–Claisen/Diels–Alder cascade. The development of a palladium catalyzed cross-coupling of methoxy alkynyl zinc reagents allows for the protecting-group-free syntheses of transtaganolides C and D. Syntheses of transtaganolides C and D are accomplished in a single operation to generate three rings, two all-carbon quaternary centers, and four tertiary stereocenters from a monocyclic, achiral precursor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Gordon et al have obtained basiliolide C via an Ireland-Claisen/Diels-Alder cascade. 73 The use of a palladium-catalysed cross-coupling of methoxy alkynyl zinc reagents allowed the protecting group-free syntheses of transtaganolides C and D by generating three rings, two all-carbon quaternary centres, and four tertiary stereocentres from a monocyclic, achiral precursor. 73 The same compounds have been obtained by Larsson et al following a biomimetic approach.…”
Section: Er Stress In Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gordon et al have obtained basiliolide C via an Ireland-Claisen/Diels-Alder cascade. 73 The use of a palladium-catalysed cross-coupling of methoxy alkynyl zinc reagents allowed the protecting group-free syntheses of transtaganolides C and D by generating three rings, two all-carbon quaternary centres, and four tertiary stereocentres from a monocyclic, achiral precursor. 73 The same compounds have been obtained by Larsson et al following a biomimetic approach.…”
Section: Er Stress In Neurodegenerative Diseasesmentioning
confidence: 99%
“…73 The use of a palladium-catalysed cross-coupling of methoxy alkynyl zinc reagents allowed the protecting group-free syntheses of transtaganolides C and D by generating three rings, two all-carbon quaternary centres, and four tertiary stereocentres from a monocyclic, achiral precursor. 73 The same compounds have been obtained by Larsson et al following a biomimetic approach. 74 Other groups conducted a cyclopropanation/ring opening strategy for establishing the stereogenic centers at C 8 and C 9 , and a biomimetic 2-pyrone Diels-Alder cycloaddition for the synthesis of the ABD ring system, with subsequent biomimetic intramolecular O-acylation for the C ring formation.…”
Section: Er Stress In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Similarly, in 2014 the Stoltz group disclosed a Negishi coupling between methoxyethynyl zinc chloride and a vinyl iodide; they noted that a xantphos ligand minimized polymerization of the alkyne due to its large bite angle. 20, 21 Following their lead, we evaluated chelating diphosphines in the series Ph 2 P-(CH 2 ) n -PPh 2 and found that the yield in the Negishi coupling correlated with the bite angle. Under optimized conditions, 1,6-bis(diphenylphosphine)hexane (dpph) ligand afforded adamantyl anisolyl ynol ether 18b in 80% yield (Scheme 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Further, Gordon et al [ 43 ] shortened the total synthesis of transtaganolide and basiliolide class-compounds through Ireland-Claisen rearrangement (ICRA) and Diels–Alder cascade approaches as described in Scheme 14 . Initially, the pyrone Diels–Alder substrate 92 with electron donating groups was achieved by Negishi cross-coupling, and the subsequent one-pot tandem ICRA and Diels–Alder sequence reactions resulted in 2:1 diastereomeric mixture of transtaganolides C ( 95 ) and D ( 96 ).…”
Section: Diels–alder Approach Of α-Pyrone To the Pragmatic Synthesis ...mentioning
confidence: 99%